Prussian Palimpsests: Historic Architecture and Urban Spaces in East Germany, 1945–1961. Issue 2 (29th June 2017) - Colla, Marcus
Abstract: This article considers the fate of Prussian buildings and memorials in East Germany between 1945 and 1961. Analyzing a number of case studies from Berlin and Potsdam, it places the treatment of these structures within the broader contours of history management practices. Although this era was characterized by a strong anti-Prussian sentiment in the GDR's historical discourse, it also witnessed a complex interaction between the SED and its historical inheritance. This interaction often influenced decisions about the fate of Prussian structures in the GDR as much as any animosity toward Prussia as a historical entity did. Abstract : Dieser Artikel beschäftigt sich mit dem Schicksal bedeutender preussischer Gebäude und anderer architektonischer Strukturen in Ostdeutschland zwischen 1945 und 1961. Unter Verweis auf Fallstudien aus Berlin und Potsdam wird die Behandlung solcher Strukturen in den größeren Rahmen der ostdeutschen Geschichtspolitik gesetzt. Obwohl diese Ära von einer stark antipreussischen Stimmung durchzogen war, war sie zugleich von einer komplexen Interaktion zwischen der SED und ihrem historischen Erbe geprägt. Oftmals beeinflusste diese Interaktion Beschlüsse und Entscheidungen über das Schicksal preussischer Strukturen in der DDR in gleichem Maße wie Feindseligkeiten gegen Preußen als historisches Gebilde.